Performance Evaluation of Crumb Rubber Asphalt Modified with Silicone-Based Warm Mix Additives. (30th September 2020) - Lushinga, Nonde; Cao, Liping; Dong, Zejiao; Yang, Chen; Assogba, Cyriaque O.
Abstract : This research was conducted to elucidate better understanding of the performance of crumb rubber asphalt modified with silicone-based warm mix additives. Two different silicone-based warm mix asphalt (WMA) additives (herein Tego XP and Addibit) were used to prepare crumb rubber modified (CRM) warm mix asphalt binders. The viscosity of these CRM binders was measured at different temperatures and shearing rates. Furthermore, softening point and penetration tests, Multiple Stress Creep Recovery (MSCR), Time Sweep (TS), Atomic Force Microscopy (AFM), Frequency sweep (FS), and Fourier Transform Infrared (FTIR) tests were also conducted on prepared samples. Based on these robust and rigorous laboratory experiments, it was established that viscosity of CRM binders was reduced by addition of Tego XP and Addibit WMA additives. However, WMA additives had different influence on rheological properties of the binder. CRM binder with Tego XP improved resistance to rutting of the binders but would degrade the fatigue performance. On the contrary, viscoelastic continuum damage (VECD) model results and those of phase angle approach revealed that the binder with Addibit improved resistance to fatigue cracking of the binders but had no adverse effects on high temperature rutting performance. FTIR test results established a presence of polydimethylsiloxane (PDMS) in CRM binders with Tego XP and Addibit. PDMS is a well-known hydrophobic organic and inorganic polymer that is water repellent; therefore, binders containing these silicone-based warm mix additives could be beneficial in resisting moisture damage in asphalt binders and mixtures. Morphology of CRM binders with and without WMA revealed good distribution of the rubber particles in asphalt binder matrix. Further addition of WMA increased surface roughness of the binder, which can be correlated to changes in microstructure properties of the binder. Therefore, the study concluded that addition of Tego XP and Addibit reduces viscosity and improves mechanical properties of the asphalt binder.